Influence of digestion temperature and organic loading rate on the continuous anaerobic treatment of process liquor from hydrothermal carbonization of sewage sludge. (December 2015) - Wirth, Benjamin; Reza, Toufiq; Mumme, Jan
Highlights: Process liquor from HTC of sewage sludge was used in anaerobic mono-digestion. Different digestion temperatures (37 and 55 °C) had no distinct effect. Step-wise decreasing HRTs from 34 to 5 days were achieved without performance loss. COD removal efficiency stabilized at 68–75% even at only 5 days HRT. Sewage sludge HTC liquor provides sufficient amounts of macro- and micronutrients. Abstract: This experimental study investigates the use of process liquor from hydrothermal carbonization (HTC) of sewage sludge as sole substrate for anaerobic digestion (AD). The process performance at 37 °C (mesophilic) and 55 °C (thermophilic) was determined based on two identical continuously-fed anaerobic filters (26 L each) operated for 20 weeks. During operation, the organic loading rate was stepwise increased from 1 to 5 gCOD L −1 d − 1 . This decreased the hydraulic retention time from 34 to 5 days. Significant differences in methane production were not observed as both reactors yielded up to 0.18 LCH4 gCOD − 1 . Increased temperature had no effect on the steady-state COD removal efficiency with both reactors stabilized at 68–75%. Macro- and micronutrients were provided by HTC liquor in sufficient concentrations throughout the experiment. Methanogenesis was identified as the speed-limiting step in anaerobic digestion of HTC liquor. Hydrolysis was of an order of magnitude faster than methanogenesis.